The TgAMPK-TgPFKII axis essentially regulates protein lactylation in the zoonotic parasite Toxoplasma gondii - Chenghuan Li; Yang Zhao; Qilong Li; Ran Chen; Ying Feng; Xiaoyu Sang; Xiangrui Li; Bang Shen; Ning Jiang; Qijun Chen (Microbiology Spectrum)
ABSTRACT Toxoplasma gondii infects nucleated cells of warm-blooded animals and cause zoonotic toxoplasmosis. Lysine lactylation, as a novel post-translational modification, is essential for epigenetic regulation and cellular processes, and proteomic analyses have shown that lactylated proteins are involved in a wide range of biological processes including energy metabolism, gene regulation, and protein biosynthesis. Additionally, protein lactylation is prevalent in T. gondii, while its regulatory mechanisms have not been fully understood. In this study, we investigated the role of T. gondii phosphofructokinase-2 (TgPFKII) and the adenosine-5’-monophosphate-activated protein kinase (AMPK) signaling pathway in the invasion, replication, and lactylation regulation of T. gondii. We localized TgPFKII in the cytoplasm of T. gondii tachyzoites and demonstrated its necessity for parasite growth and protein lactylation through auxin-induced degradation. Our results showed that inhibition of the AMPK pathway led to decreased TgPFKII expression and reduced protein lactylation levels. Furthermore, AMPK-specific inhibitors significantly impaired parasite invasion and proliferation. These findings highlight TgPFKII as a crucial regulator of lactylation and underscore the importance of the AMPK pathway in T. gondii’s pathogenic mechanisms, offering potential targets for therapeutic intervention.IMPORTANCEUnderstanding the intricate mechanisms by which Toxoplasma gondii invades and proliferates within host cells is essential for developing novel therapeutic strategies against toxoplasmosis. This study focuses on the pivotal roles of T. gondii phosphofructokinase-2 (TgPFKII) and the adenosine-5’-monophosphate-activated protein kinase (AMPK) signaling pathway in regulating protein lactylation in association with parasite invasion and growth. By elucidating the cellular localization and functional importance of TgPFKII, as well as its regulation through AMPK-specific inhibitors, we provide comprehensive insights into the metabolic and signaling networks that underpin T. gondii pathogenicity. Our findings reveal that TgPFKII is a critical regulator of lactylation and that the AMPK pathway significantly influences T. gondii’s ability to invade and replicate within host cells. These insights pave the way for targeted interventions aimed at disrupting key metabolic and signaling pathways in T. gondii, potentially leading to more effective treatments for toxoplasmosis.